Pengaruh Penerapan Konseling Kelompok dengan Cognitive Restructuring untuk Meningkatkan Pengendalian Emosi Negatif - Aisha Azizah Adriani Mahardika; Yasintha Sari Pratiwi; Wahyu Widyatmoko; Muhaimin Abdillah (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the effect of implementing cognitive restructuring techniques through Cognitive Behavioral Therapy (CBT)-based group counseling services on improving students' negative emotional control. The study used a pre-experimental method with a one-group pretest-posttest design, conducted at SMP Negeri 7 Samarinda. The study sample, consisting of six students, was determined through purposive sampling, taking into account the number of group counseling members stipulated in the guidance and counseling operational guidelines. The research instrument was a negative emotional control scale, while data analysis used a normality test and a paired sample t-test. The results showed that the average negative emotional control score before treatment increased from 101.2 (low category) to 158.5 (very high category) after treatment. The paired sample t-test showed a significance value of 0.000 <0.05, indicating that the implementation of cognitive restructuring techniques in CBT-based group counseling services has a positive effect on improving students' negative emotional control. Therefore, cognitive restructuring techniques can be implemented as a strategy in guidance and counseling services in schools to help improve students' negative emotional control.